eCM 2021
DOI: 10.22203/ecm.v042a03
|View full text |Cite
|
Sign up to set email alerts
|

Non-contact induction heating and SAAP-148 eliminate persisters within MRSA biofilms mimicking a metal implant infection

Abstract: Implant-associated infections are the primary cause of complications following orthopaedic surgery. Due to biofilm and persister formation, current treatments, i.e. surgical debridement followed by antibiotics, often fail. There is an urgent need for alternative strategies to combat such infections. Therefore, the present study investigated the effects of non-contact induction heating (NCIH), the antimicrobial peptide SAAP-148 and combinations thereof on bacterial counts in 7 d mature biofilms and in persister… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…SAAP-148 and halicin were effective against these persisters derived from the antibiotic-exposed mature biofilms of the four bacterial strains tested in a dose-dependent manner. This is in agreement with earlier findings that SAAP-148 effectively reduced bacterial counts within antibiotic-exposed mature biofilms of MRSA [37,38]. Herein, we provided proof for the first time that SAAP-148 possesses a potent anti-persister effect against GNB strains.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…SAAP-148 and halicin were effective against these persisters derived from the antibiotic-exposed mature biofilms of the four bacterial strains tested in a dose-dependent manner. This is in agreement with earlier findings that SAAP-148 effectively reduced bacterial counts within antibiotic-exposed mature biofilms of MRSA [37,38]. Herein, we provided proof for the first time that SAAP-148 possesses a potent anti-persister effect against GNB strains.…”
Section: Discussionsupporting
confidence: 92%
“…In a study by de Breij et al [28], the peptide SAAP-148 was highly efficient in killing a panel of planktonic multidrug-resistant (MDR) bacteria, including colistin-resistant E. coli, K. pneumoniae, and A. baumannii. Further studies have also shown the efficacy of this peptide against biofilms [28,36] and persister cells [28,37,38]. de Breij et al [28] investigated the mode of action of SAAP-148 and showed that the formation of pores in cell walls led to the permeabilization of the membrane, followed by the destruction of the bacterial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, 100 µL of mid-logarithmic phase MRSA and MSSA at 10 7 CFU/mL in BHI broth was added on top of medical grade titanium-7% aluminum-6% niobium [TAN; iso5832/11 discs, handled as described previously 30 ] in 96-wells flat-bottom polystyrene plates. After 1 h, TAN discs were washed twice with 0.9% saline to remove non-adherent bacteria and transferred to a 96-wells flat-bottom polystyrene plate with 100 µL of ISP at final concentrations ranging from 10 1 –10 8 PFU/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Many other compounds have been found to possess anti-persister activity, including synthetic peptides like SAAP-148 and natural analogs like Pexiganan 106,107 .…”
Section: Targeting Dormant Cellsmentioning
confidence: 99%